PENERAPAN PROSES KOGNITIF DAN TERAPI COGNITIVE BLOCKING DALAM PENINGKATAN KUALITAS PEMBELAJARAN MENULIS - Sibarani, Berlin (Diksi, 2015)
Students in general have difficulty in expressing their ideas in writing. This indicates that the teaching of writing is not yet successful. The lack of success is due to, among others, the dominance of theoretical explanation and discussion of how to develop good paragraphs and how to use punctuation correctly in classes of writing. Such teaching behavior may be urged by an underlying belief that knowledge of writing and mastery of the language used are the main factors determining writing ability. But current research results indicate that writing is a cognitive process greatly determined by the thinking or reasoning ability. So the process of writing will be hindered when the process of reasoning experiences a dead end or cognitive blocking. On the other hand, a reasoning process which runs well produces ideas which then demand expression. The pressure for expression urges the owner of the ideas to study good language use and how to express ideas in an organized way. Therefore, the teaching of writing had better focus on improving thinking quality and minimizing cognitive blocking. Keywords: the teaching of writing, cognitive blocking